Miss Gadget-Tech Enterprise: Service And Repair Gadget / Nur Syafiqah Azhar [et al.] - Azhar, Nur Syafiqah; Hamedon, Syasya Nadhirah; Zamri, Siti Nurul Suhada; Mohd Shahar, Ili Syahirah (2017)
Miss Gadget-Tech is a company which focus on service handphones and laptops. First and foremost, this generation are more interested in using latest technologies. So, we took this opportunity to give our best services for them on repairing their gadgets especially their smartphones.